Peranan Psikologi Dalam Mengatasi Kejenuhan Siswa Dalam Belajar - Putri, Sari Wulandari; Binawati, Ni Wayan Sariani Binawati (Metta : Jurnal Ilmu Multidisiplin, 2024)
Learning is an activity carried out by an individual every day, but in the learning process various problems are often encountered in the process of changing behavior. One of them is the feeling of boredom experienced while carrying out the learning process. The problem of learning boredom experienced by students is one of the obstacles that makes the quality of student learning outcomes low. Factors that cause boredom in learning include lack of motivation in the learning process, low teacher creativity in presenting interesting material in the learning process. So that this does not become a distraction in the student's learning process, the role of psychology is used in overcoming the boredom experienced by students in learning. Solving these problems, this research uses a qualitative research approach with literature study. The data sources for this research are the results of research or writings by researchers or previously written library materials with descriptive argumentative data analysis techniques. The results of this research show that there are three points, namely 1) boredom and fatigue affect student learning outcomes, 2) students need to know themselves, and 3) students need encouragement both from within themselves and from outside themselves. Therefore, there are tips for overcoming student boredom in learning activities using a perspective from psychology, including; psychology provides direction to teachers in determining approaches, psychology makes the learning process more effective, provides opportunities for students to absorb information more quickly, psychology as a tool for evaluating learning strategies, psychology can provide a way to adapt, psychology can be used as a tool to provide motivation, provide reward and punishment, gives direction in trying to know oneself.